Transitional Justice Studies: Development, Challenges, and Future Directions - Strupinskienė, Lina (Politologija, 2024)
In an era marked by numerous conflicts and human rights violations, this article provides a comprehensive review of transitional justice studies, assessing the evolution of the field and exploring potential future directions. It addresses several critical questions: How has the field of transitional justice developed, and what factors have influenced its changes over time? What tools and techniques have been employed, and what challenges and achievements have they revealed? What significant lessons and recommendations have emerged from existing studies, and why are they important? Finally, the article also considers normative aspirations for future cases of transitional justice, particularly in the context of Russia’s war against Ukraine. This analysis underscores the belief that academic self-reflection is valuable not only for students and researchers but also for national and international actors involved in implementing transitional justice strategies.
Keywords: Transitional Justice; Russian war in Ukraine; Sustainable Peace and Reconciliation; Conflict Resolution